Mycena quercophila , a new species of Mycena section Polyadelphia growing on Quercus ilex leaves - Vlllarreal, M (Österreichische Zeitschrift für Pilzkunde, 1997)
Mycena quercophila, a member of Mycena section Polyadelphia, is proposed as new. It is characterized by brownish yellow colours of the fruitbodies and smooth to sparsely diverticulate chei- locystidia. Most species of this section show profusely diverticulate cheilocystidia. except the related M terenu. with completely smooth cheilocystidia and with different colours and habitat. A colour figure and microscopical drawings of the new species are added
Keywords: Agaricales; Basidiomvcetes; Mycena quercophila; Mycoflora of Spain; new species; systematics; taxonomy; Trichulomataceue